Somali piracy and terrorism in the Horn of Africa - Daniels, Christopher L., 1982- (Global flashpoints., 2012)
This book provides readers with a comprehensive and in-depth analysis of the spate of piracy and terrorism plaguing the waters of Somalia and the global threat posed by this activity. Contesting the commonly held perception that the piracy and terrorism occurring in Somalia are two separate and unrelated activities, Daniels reveals how the collapse of the Somali state and the chaos that has ensued created the environment for piracy and terrorism to flourish in combination. He also notes how the failure to restore a functioning central government has allowed both to become dan.